Primary Immunodeficiency Diseases in Highly Consanguineous Populations from Middle East and North Africa: Epidemiology, Diagnosis, and Care - Al-Mousa, Hamoud; Al-Saud, Bandar (Frontiers in Immunology, 2017)
Middle East and North Africa region (MENA) populations are of different ethnic origins. Consanguineous marriages are common practice with an overall incidence ranging between 20 to 50%. Primary immunodeficiency diseases (PIDs) are a group of heterogeneous genetic disorders caused by defects in the immune system that predispose patients to recurrent infections, autoimmune diseases and malignancies. PIDs are more common in areas with high rates of consanguineous marriage since most have an autosomal recessive mode of inheritance. Studies of PIDs in the region had contributed into the discovery and the understanding of several novel immunodeficiency disorders. Few MENA countries have established national registries that helped in estimating the prevalence and defining common PIDs phenotypes. Available reports from those registries suggest a predominance of combined immunodeficiency disorders in comparison to antibody deficiencies seen in other populations. Access to a comprehensive clinical immunology management services is limited in most MENA countries. Few countries had established advanced clinical immunology service, capable to provide extensive genetic testing and stem cell transplantation for various immunodeficiency disorders. Newborn screening for PIDs is an essential need in this population considering the high incidence of illness and can be implemented and incorporated into existing newborn screening programs in some MENA countries. Increased awareness, subspecialty training in clinical immunology and establishing collaborating research centers are necessary to improve patient care. In this review we highlight some of the available epidemiological data, challenges in establishing diagnosis, and available therapy for PID patients in the region.